A Systematic Review of Green Brand Evangelism: Definitions and Drivers - Rennyta Yusiana; Rennyta Yusiana; Ratih Hurriyati; Disman Disman; Lili Adi Wibowo; Arry Widodo; Ni Putu Nurwita Pratami (Fakultas Ekonomi dan Bisnis Islam, 2025)
Environmental sustainability has become a central concern in global markets, driving scholars and practitioners to explore how consumers can act as active promoters of sustainable brands. Green Brand Evangelism (GBE) captures this phenomenon, defined as consumers’ voluntary and enthusiastic advocacy of eco-friendly brands. Despite its relevance, research on GBE remains fragmented, with inconsistent definitions and scattered insights into its drivers. This paper addresses two research questions: How is GBE defined in the extant literature, and what are the enablers that foster it? This study provides the first systematic literature review (SLR) focused exclusively on GBE, consolidating fragmented evidence across contexts and reconceptualizing GBE as a multidimensional construct. Following PRISMA guidelines, eleven peer-reviewed articles (2020–2025) were synthesized from multiple databases. Data were analyzed thematically around two research questions and complemented with a bibliometric keyword co-occurrence analysis (VOSviewer). GBE emerges from the interplay of individual, brand, and contextual enablers. The study advances theoretical clarity and offers practical implications for managers, marketers, and policymakers in cultivating consumers as green brand evangelists.